Social eCommerce - Spencer, Stephan M.; Sheahan, Jennifer; Harding, Jimmy (O'Reilly Media, 2014)
Discover how to extend brand reach and forming key business relationships through social media. With this guide, two highly respected experts in ecommerce, online marketing, and social media clearly explain how to increase online sales using social media, complete with case studies.